1991
DOI: 10.1083/jcb.114.1.101
|View full text |Cite
|
Sign up to set email alerts
|

CAL1, a gene required for activity of chitin synthase 3 in Saccharomyces cerevisiae.

Abstract: Abstract. The CALI gene was cloned by complementation of the defect in Calcofluor-resistant calR1 mutants of Saccharomyces cerevisiae. Transformation of the mutants with a plasmid carrying the appropriate insert restored Calcofluor sensitivity, wild-type chitin levels and normal spore maturation. Southern blots using the DNA fragment as a probe showed hybridization to a single locus. Allelic tests indicated that the cloned gene corresponded to the calRI locus . The DNA insert contains a single open-reading fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
169
0
1

Year Published

1993
1993
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(175 citation statements)
references
References 40 publications
5
169
0
1
Order By: Relevance
“…S. cerevisiae strain W303 (MATa trp1 leu2 ura3 his3 ade2) was used as wild-type control. Strain TCY1 (MATa trp1 leu2 ura3 his3 ade2 chs3::LEU2) was created by LEU2 replacement of CHS3 as follows: the CHS3 gene from pHV7 [11] was cloned as an EcoRIϪ SphI fragment of 5.6 kb into the Stratagene vector pBluescript II KS (ϩ) (plasmid pTC1). The XhoIϪPstI fragment from CHS3 (nucleotides 519Ϫ2909) from pTC1 [12] was replaced by the LEU2 marker; this plasmid was digested with MluI and the 4.6-kb fragment that included the chs3::LEU2 construct was purified and transformed into strain W303 [13].…”
Section: Methodsmentioning
confidence: 99%
“…S. cerevisiae strain W303 (MATa trp1 leu2 ura3 his3 ade2) was used as wild-type control. Strain TCY1 (MATa trp1 leu2 ura3 his3 ade2 chs3::LEU2) was created by LEU2 replacement of CHS3 as follows: the CHS3 gene from pHV7 [11] was cloned as an EcoRIϪ SphI fragment of 5.6 kb into the Stratagene vector pBluescript II KS (ϩ) (plasmid pTC1). The XhoIϪPstI fragment from CHS3 (nucleotides 519Ϫ2909) from pTC1 [12] was replaced by the LEU2 marker; this plasmid was digested with MluI and the 4.6-kb fragment that included the chs3::LEU2 construct was purified and transformed into strain W303 [13].…”
Section: Methodsmentioning
confidence: 99%
“…Similar to the b-1,3 glucan chains of the b-glucan layer, the b-1,4-linked glucosamine chains of the chitosan layer are synthesized by an integral membrane enzyme that binds nucleotide sugars in the cytoplasm and extrudes the polymer to the extracellular space (Orlean 1997). In vegetative cells, cell wall chitin is produced by three different chitin synthases: Chs1, Chs2, and Chs3 (Silverman et al 1988;Cabib et al 1989;Silverman 1989;Shaw et al 1991;Valdivieso et al 1991). During sporulation, chitosan synthesis is mediated solely by Chs3 (Pammer et al 1992).…”
Section: Membrane-cytoskeletal Interactionsmentioning
confidence: 99%
“…Kronstad et al (1987) demonstrated that at least two copies of the pheromone-responsive element were required for the full level a-factorenhanced BAR1 gene expression. Interestingly, pheromoneresponsive elements could also be identified in the upstream regions of three genes involved in chitin synthesis: GFAU GCNl encoding L-glutamine:fructose-6-phosphate amidotransferase (Watzele and Tanner, 1989), CHSl encoding chitin-synthase I (Bulawa et al, 1986;Appeltauer and Achsstetter, 1989) and CSD2 which is essential for chitin synthase 111 activity (Valdivieso et al, 1991 ;Orlean, 1987). Furthermore, Orlean et al (1985) observed that mating factors increase the de novo synthesis of amino sugars.…”
Section: Discussionmentioning
confidence: 99%